Subjectivity Formation of a Technical University Master’s Student: A New Challenge for Engineering Education - L. K. Geykhman; V. S. Kabanov (Высшее образование в России)
An important condition for the digital transformation of education is the subjectivity of students and teachers. The formation of subjectivity as the ability to set one’s own goals and change either oneself or the educational environment to achieve them raises a number of questions: what is meant by the subjectivity of a student and a teacher, what does it mean to be a subject of the educational process, which factors contribute to and which hinder the formation of subjectivity. The authors focus on the conditions that promote and prevent the formation of subjectivity in master’s education of future engineers. Based on a review of foreign and domestic approaches to understanding subjectivity and the conditions for its development, it is concluded that all researchers distinguish similar aspects and manifestations in subjectivity: motivational (intrinsic motivation), emotional-valuable (proactive and responsible attitude to life), regulatory (the ability to set goals and follow them through to the end), cognitive (desire and ability to apply knowledge) and practical (skills, experience of independent activity). It has been established that foreign studies more often consider subjectivity as a resource, which improves the quality of education, while Russian studies consider it as a goal and a result of education. The article describes a taxonomy of subjectivity, which allows to measure it as an educational result. Based on the analysis of necessary and sufficient conditions for subjectivity formation, the hypothesis is made that the sufficient condition for subjectivity formation in mastering the “pedagogics” discipline is stepwise equitable partnership between all subjects of educational process. The condition is specified as a sequence of actions of a teacher and a master’s student in the process of mastering the discipline. The article describes the results of a pedagogical experiment in a group of master’s students of PNRPU Faculty of Civil Engineering, aimed at testing the proposed conditions. The results obtained show that step-bystep organized peer-to-peer interaction enabled most students in the experimental group to achieve the subjectivity level by the end of the discipline, while in the control group most students reached only the objectivity level. The motivational and practical aspects of subjectivity changed most significantly in the experimental group.